2020
DOI: 10.1101/2020.08.31.276642
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prophylactic Application of Tailocins Prevents Infection byPseudomonas syringae

Abstract: Tailocins are phage-derived bacteriocins that demonstrate great potential as agricultural antimicrobials given their high killing efficiency and their precise strain-specific targeting ability. Our group has recently categorized and characterized tailocins produced by and tailocin sensitivities of the phytopathogen Pseudomonas syringae, and here we extend these experiments to test whether prophylactic tailocin application can prevent infection of Nicotiana benthamiana by P. syringae pv. syringae B728a. Specifi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…The single colony was then grown overnight in KB media plus rifampicin and frozen in 40% glycerol at -80˚C. The creation of DBL1424 (a Rbp/chaperone deletion mutant of USA011R) and DBL1701 (a complementation strain derived from DBL1424) was described in (Baltrus et al 2022). These two genes are located at the 3' end of a predicted tailocin operon and have also been shown that they are oftentimes exchanged together, allowing for simplicity of complementation (Baltrus et al 2018).…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
“…The single colony was then grown overnight in KB media plus rifampicin and frozen in 40% glycerol at -80˚C. The creation of DBL1424 (a Rbp/chaperone deletion mutant of USA011R) and DBL1701 (a complementation strain derived from DBL1424) was described in (Baltrus et al 2022). These two genes are located at the 3' end of a predicted tailocin operon and have also been shown that they are oftentimes exchanged together, allowing for simplicity of complementation (Baltrus et al 2018).…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
“…In particular, the regulatory implications are far simpler and end users have the flexibility to decide where, when and what crops they wish to treat. Glasshouse experiments have demonstrated that phage‐like bacteriocins (tailocins) directly applied to tomato and tobacco are highly effective at protecting against important plant phytopathogenic bacteria 44,45 . Tailocins are multicomponent bacteriocins, making them difficult to produce in large‐scale in other model organisms 46 .…”
Section: Applications Of Protein Antibiotics In the Fieldmentioning
confidence: 99%
“…2 A number of studies report the use of phages to treat specific plant pathogens. [3][4][5][6][7] These studies indicate a potential for prophylactic use of phages in plants.…”
Section: Use Of Phages In Plantsmentioning
confidence: 99%